"Unraveling the Threads: Behind Divorce by Lawsuit at the Religious Court of Sidenreng Rappang Regency" - Putri Alfiah (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
The aim of this research is to identify the main factors contributing to the increasing number of divorce cases filed by wives (petition for divorce) at the Religious Court of Sidenreng Rappang. The method employed is qualitative descriptive, involving data collection through literature review and in-depth interviews with wives filing for divorce. The research findings indicate several reasons behind divorce filings, including economic factors, domestic disputes or conflicts, presence of a third party or infidelity, and domestic violence. Additionally, the literature review suggests that couples intending to marry tend to perceive pre-marital education as a formality, while those who have divorced admit to lacking a true understanding of the meaning of marriage.